Cardiac Mechanics in Patients with Systemic Hypertension with Normal EF: A Speckle - Strain Imaging Study - Raghvendra Choudhary; Deepak Maheshwari; Puneet Rijhwani; Monika Rathore (Journal of Hypertension and Cardiology, 2013)
Background: Conventional transthoracic echocardiography (TTE) and tissue Doppler imaging (TDI) are usually unable to reveal very early subtle abnormalities in left ventricular (LV) systolic function caused by hypertension, prior to manifestation of hypertrophy (LVH). This study was undertaken to assess whether speckle tracking echocardiography (STE) provides more insight into early hypertension induced LV systolic dysfunction, with the purpose of identifying patients at higher risk for heart failure (HF). Methods: Fifty patients (54.16 ± 8.4 years) and 50 controls (52.17 ± 8.6 years) were enrolled. According to the presence or absence of LVH, patients were classified as LVH(+) and LVH(–), respectively. Global longitudinal function was calculated by TDI, global strains (longitudinal (LS), radial (RS), and circumferential (CS)) were assessed by STE. Results: Conventional TTE showed a normal systolic function in all patients. TDI was able to detect a systolic dysfunction only in the LVH(+) group (P < 0.001) whereas STE revealed an impairment of systolic LS and CS in all patients, including those without hypertrophy (P =<0.0001). Furthermore, in the LVH(+) group, STE showed increased RS . Conclusion: In hypertensive patients, STE provides more detailed information than conventional echocardiography and TDI, since it reveals a systolic dysfunction before hypertrophy occurs (Stage A of ACC/AHA classification of HF) and identifies some early LV mechanic changes that might improve the clinical management of these patients
Keywords: hypertension